Morphometric analysis and fabrication of prosthetic ear using CAD/CAM and additive manufacturing technology - Mohamed, Nor Azura (2016)
Prosthetic ear rehabilitation is one of the treatments for auricular defect. Current practice by surgeon require patient to go for osseointegrated craniofacial implant surgery for retention of the prosthetic ear. Traditionally, the wax pattern was created from the impression taken from patient and the final prosthesis is processed with silicone material. This conventional method has always been time consuming, massive work and caused discomfort to patient. Moreover the accuracy of the final prosthetic sometimes was not satisfied. Impression technique play a vital role in determining accurate reproduction of affected and unaffected ears, orientation of the ear during wax try in and fabrication of ear prostheses. Hence, the ear anthropometric data is important to determine the correct orientation and position of the prosthetic ear. This paper aims to provide morphometric data of a few standard ear parameters for Kelantanese and also describes a novel method of design and fabricating the prosthetic ear applying CAD/CAM and additive manufacturing technologies. A clinical study is done onto a patient in HUSM and comparison is made between traditional method and the new approach using computer aided technology. Study also validates the prosthetic ear obtained from both techniques with the morphometric data. The measurement technique of the final prosthetic ear to validate the result with regards to the morphometric data was done digitally using software. Morphometric study was conducted on 68 samples of normal ear for bothleft and right with 15 parameters measured. Data was retrieved from CT scan and convert to 3D image using soft tissue development. Mirror image technique was applied to reconstruct the missing ear, and then fabricate the 3D model of the prosthetic ear using Stereolitography (SLA) technology. The 3D model will become the master mold to produce the final prosthetic ear using vacuum casting technology. Morphometric analysis gave the mean and standard deviation values for auricular length and width, length and height of tragus, insertion length of auricle, length and width of lobular and conchal, protusion at superaurale and tragal level as well as the inclination and symmetrical angle. While study also illustrates that there is significant different between traditional and computer aided approach. The new method shows time reduction during design and fabrication stage and also show improvement in accuracy and aesthetic appearance.